Sugary snack restriction enhances body composition improvement in overweight women engaging in non-face-to-face walking during COVID-19 - Lee, Youngjun; Kim, Nahyun; Go, Seunghwan; Kim, Jisu; Park, Jonghoon (Frontiers in Public Health, 2024)
Introduction This study assesses the impact of dietary modification, specifically sugary snack restriction, in conjunction with a brisk walking program on overweight management in young overweight women, with a focus on changes in body composition and glucose metabolism. Method An 8-week randomized controlled trial was conducted amidst the COVID-19 pandemic, utilizing a remote intervention approach to comply with health guidelines and ensure participant safety. The study’s remote nature highlights adaptability in health interventions during challenging periods, such as the COVID-19 pandemic. Twenty-one overweight Korean women aged 20–39, with an average BMI of 24.6, were selected for the study. They were divided into two groups: one engaging in brisk walking and the other combining this exercise with a sugary snack restriction, demonstrating the study’s focus on comparative intervention efficacy. Results The exercise-only group showed notable reductions in glucose, insulin, HOMA-IR (p < 0.05), and total cholesterol levels (p < 0.01). In contrast, the group that combined exercise with dietary modification displayed more pronounced improvements in body weight, fat mass, and waist circumference (p < 0.05). This differential outcome emphasizes the added benefit of integrating dietary control with physical activity. Discussion The findings suggest that adding a dietary component, particularly a sugary snack restriction, to an exercise regimen can significantly enhance the effectiveness of overweight management in young women. This study underscores the importance of holistic lifestyle interventions that combine dietary and physical activity modifications for improved health outcomes.